PENGARUH PROFITABILITAS, KEPEMILIKAN KELUARGA DAN CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK DI INDONESIA - Saputra, Made Dana; Susanti, Jeni; Istiarto, Istiarto (Valid Jurnal Ilmiah, 2019)
This study aims to determine the effect of profitability of Family and Corporate Governance to tax avoidance in companies listed on the Indonesia Stock Exchange 2012-2016. The elements of corporate governance contain the proportion of the board of commissioners, and the committee audit, while profitability contains return on assets and family ownership. The sample of this research is property company, real estate, and building construction which listed in Indonesia Stock Exchange year 2012-2014. The sample that is built is not experiencing losses and selected by purposive sampling. Data analysis used multiple regression to test the hypothesis. The results show that Profitability, Family Ownership and Corporate Governance significantly influence tax avoidance